The Fighting Sullivans : How Hollywood and the Military Make Heroes - Kuklick, Bruce, 1941- (Book collections on Project MUSE., 2016)
"The five Sullivan brothers, at their insistence, were assigned to the same ship in World War II. Predictably when the ship was blown up they all were killed. The Navy buried their mistake in allowing all five to serve on the same ship by turning the five brothers into heroes, complete with a ship named after them, a Hollywood movie, and news coverage that turned five shiftless losers into great American heroes. Kuklick tells the story of who they were, what happened to them, and how they were transformed into heroes by the war publicity machine and Hollywood. He focuses a lot on the film The Fighting Sullivans telling how it got made, how it related to the use of Hollywood in the effort to promote the war, and how the film and the brothers' story was received. He also tells about the continuing half-life of their fame as their dying hometown, Waterloo, Iowa, tried to capitalize on their fame, much to the chagrin of some of some townspeople who remember the real Sullivan brothers. This is a book about the manufacture of heroes in war-time America."--Provided by publisher.